Acyl Radical Addition to Activated Olefins: A Stereocontrolled Route to Polysubstituted Tetrahydrofurans and Lactones, and Application to the Total Synthesis of (+)‐No. 2106 A. Issue 10 (13th March 2017) - Grélaud, Simon; Lusseau, Jonathan; Landais, Yannick
Abstract : The addition of acyl radicals to α, β‐unsaturated esters, followed by acetalization and reduction of the resulting hemiacetal was shown to provide a straightforward access to tetrahydrofurans, and fused tetrahydrofuran–lactones in good yield with high 1, 3‐stereocontrol. Similar addition reactions to five‐ and six‐membered‐ring α‐methylenelactones led to trisubstituted lactones with high diastereocontrol, using (Me3 Si)3 SiH as hydrogen‐atom‐transfer agent. This strategy was applied to the first total synthesis of (+)‐No. 2106 A, a fused THF–lactone produced by an endophytic fungus isolated from the seeds of the mangrove Avicennia marina . Abstract : Addition of acyl radicals to Baylis‐Hillman adducts followed by acetalization and reduction with (Me3 Si)3 SiH provides the corresponding tetrahydrofurans with moderate 1, 2‐ but high 1, 3‐stereocontrol. Similar addition to methylenelactones was shown to afford tetrahydrofuran–lactones with high stereocontrol, this strategy being then applied to the total synthesis of (+)‐no. 2106 A.